Nieostrość z perspektywy teorii komunikacji i badań normalności - Siemes, Annette (Strategie komunikacyjne i procesy twórcze, 2022)
The issue of fuzziness has not been analysed as yet from the perspective of communication theory and communication research. The article deals with the role of fuzziness in the communication process (the latter understood as the mechanizm of negotiating meanings generating the third (communicational) reality). The starting point that illustrates the broadness of the issue and its various aspects is constituted by fuzzy pictures (photographies) and (verbal) reactions referring to them. The theoretic basis is built by communication theory and research concerning normality assumptions in communication; the results of other research in the field of language and visuality serve as a wider context. The text presents the characteristics of fuzziness as a category of communication(s), where fuzziness appears both as a construct and concept (linked to a system of assumptions). The analysis against a theoretic background allows to reveal the basic functions of fuzziness for starting and perpetuating the communication process that are realized by generating connectivity (in the sense of a broad range of potential references regarding a given communicational (visual or verbal) offer). This allows to outline the research problem and guiding questions for planned further empiric investigation which might concern (a) the semantics and communicational meaning of the word “fuzziness” in concrete applications as well as (b) the functional contexts of fuzziness not only as a term, but as a concept and functional element. Possible ways of operationalization regarding research material and methods are presented for both areas.